👤

Cine rezolva tot primeste coronita!!

3 · { -9 ·[ -3·( x -12) + 8] - 12} = -9
2· { 10 - 2·[ 1 - 2· (x - 7)]} = -24
{[ -3 · (-x -1) -18] : (-2) +5} : (-4) = -5


Răspuns :

3*{-9*[-3*(x-12)+8]-12]=-9
-9*[-3*(x-12)+8]-12=-9:3
-9*[-3*(x-12)+8]=-3+12
-3*(x-12)+8=9:9
-3*(x-12)=1-8
x-12=-7:(-3)
x=7/3+12
x=7/3+36/3
x=43/3
x=14,33
2*{10-2*[1-2*(x-7)]}=-25                                                                                              
2*[10-2*(1-2x-14)]=-24
2*[10-2*(-13-2x)]=-24
2*(10+26+4x)=-24
20+52+8x=-24
72+8x=-24
8x=96
x=12


{[-3*(-x-1)-18]:(-2)+5}:(-4)=-5
[(3x+3-18):(-2)+]:(-4)=-5
(-6x/2-6/2+9+5)*(-1/4)=-5
(-6x/2-6/2+14)*(-1/4)=-5
(-6x/2-6/2+28/2)*(-1/4)=-5
6x/8+6/8-28/8=-5
6x/8-22/8=-5
6x-22=-40
6x=-18
x=3

/=supra                
Vezi imaginea RADULESCUBIANCA
Vezi imaginea RADULESCUBIANCA